Memantine transport by a proton-coupled organic cation antiporter in hCMEC/D3 cells, an in vitro human blood-brain barrier model - Higuchi, Kei; Kitamura, Atsushi; Okura, Takashi; Deguchi, Yoshiharu (Drug metabolism and pharmacokinetics, 2015)
Memantine is clinically used for the treatment of patients with Alzheimer's disease and is highly distributed to the brain. The aim of this study is to characterize memantine transport at the blood–brain barrier (BBB) using hCMEC/D3 cells, a human BBB model. The initial uptake velocity of memantine in hCMEC/D3 cells was concentration-dependent, and was reduced by metabolic inhibitors, but was independent of extracellular sodium ion and membrane potential. Intracellular alkalization and intracellular acidification markedly reduced and enhanced the uptake, respectively. The uptake was strongly inhibited by quinidine, pyrilamine and verapamil, and was moderately inhibited by TEA (substrate of OCTs and OCTNs) and l-carnitine (substrate of OCTN2), but was not inhibited by MPP+ (substrate of OCTs and PMAT) or ergothioneine (substrate of OCTN1). Although relatively abundant expression of OCTN2 gene has been observed in hCMEC/D3 cells, knockdown of OCTN2 with siRNA did not decrease memantine uptake. Memantine and diphenhydramine each showed inhibition of the other's uptake in a competitive manner. Thus, proton-coupled organic cation antiporter(s) appears to be involved in the transport of memantine in hCMEC/D3 cells, at least in part. Our results indicate that the in vivo BBB permeability of memantine in humans can be predicted from the in vitro uptake clearance in hCMEC/D3 cells.